Penerapan Model Problem Based Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Pada Pendidikan Jasmani - Dupri, Dupri; Nazirun, Novia; SM, Nova Risma (Journal Sport Area, 2019)
The low of students’ critical thinking when learning can be seen from several aspects such as the inability of students to identify a problem properly, so that the accomplishment in learning is not solved properly. The purpose of this study is to see an increase in critical thinking skills through problem based learning models in physical education learning. The method of this research is an experimental method with randomize pretest and posttest control group design. The sampling technique chosen in this research was cluster random sampling, so the samples in this study were divided into two classes: the experimental group and the control group of 68 students. The instrument that used in terms of seeing students' critical thinking skills uses written tests with true-false questions (B-S). The results of this study indicate that the problem based learning model can improve students' critical thinking skills well in physical education learning.